2020
DOI: 10.1016/j.clae.2019.10.138
|View full text |Cite
|
Sign up to set email alerts
|

A contra-lateral comparison of the visual effects of a photochromic vs. non-photochromic contact lens

Abstract: To compare the effects of a photochromic contact lens vs. a non-photochromic control lens on visual function. Methods: A subject-masked, prospective contralateral eye design was used. Sixty-one subjects were enroled based on age (using a 2:1 allocation ratio for ages 18-39 and 40-65 years, respectively). The study lenses were senofilcon A with photochromic additive (Test) that filtered over the entire lens, compared to a non-photochromic Control with no tint. The Test lens was partially activated during testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 24 publications
(28 reference statements)
2
31
0
Order By: Relevance
“…These specific visual functions were selected based on our recent studies using the same apparatus with an activated photochromic contact lens. All tests used the same apparatus, modified for each parameter (for details, see Renzi-Hammond et al 1 ). The glare source (annulus/disk; simulating noon-day sunlight) and the visual target were produced by a 1000-W xenon arc point source lamp, with a modified housing that allowed dual-channel exit (Newport Optics, Irvine, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These specific visual functions were selected based on our recent studies using the same apparatus with an activated photochromic contact lens. All tests used the same apparatus, modified for each parameter (for details, see Renzi-Hammond et al 1 ). The glare source (annulus/disk; simulating noon-day sunlight) and the visual target were produced by a 1000-W xenon arc point source lamp, with a modified housing that allowed dual-channel exit (Newport Optics, Irvine, CA).…”
Section: Methodsmentioning
confidence: 99%
“…A recent empirical study has shown that the lens demonstrates reduced visual issues, such as glare disability and discomfort, while speeding photostress recovery. 1 Renzi-Hammond et al 1 used a violet activator to test the lens as it would be expected to be darkened in a typical outdoor situation. The photochromic lenses, however, are meant to be worn inside as well.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Photochromic contact lenses can significantly reduce objective measures of squinting compared to clear contact lenses [3]. In a randomized, contralateral crossover trial, investigators measured changes in patients' palpebral fissure height 1 s into a 5 s exposure to a 1000 W xenon arc point source lamp.…”
Section: Vision Performance Itemmentioning
confidence: 99%
“…The U.S. Food and Drug Administration approved the Test lens in April 2018 [2], and studies have investigated aspects of its performance, including its effect on visual recovery, squint response, and driving [3,4]. Nonetheless, the literature is yet to report the subjective vision experience of patients fitted with this lens.…”
Section: Introductionmentioning
confidence: 99%